Pasang Surut Kerajinan Patung Kayu Pada Industri Pariwisata Di Desa Batubulan Kangin - I Wayan Arissusila; Ni Luh Putu Trisdiyani (Jayapangus Press, 2021)
The wooden sculpture craft in Batubulan Kangin Village began in 1968. The learning process was more than twenty people, and took place in Guang Village. In 1970, after they were proficient at making sculptures, they taught their villages starting with statues of Garuda, Ramayana and others. These crafts have marketing opportunities and motivate craftsmen to increase their creativity. When there was the first Bali bombing, and the globalization market, these crafts experienced a decline. Based on that, the problems were posed, namely: How is the process of realizing wooden sculptures, what products are produced, and how are the ebb and flow of wooden sculptures in Batubulan Kangin Village. The purpose of this study was to describe the ebb and flow of wooden sculpture in the tourism industry in Batubulan Kangin Village. This study uses data collection techniques carried out by observation, interviews and document studies. Data analysis was carried out with a qualitative approach, based on aesthetic theory and social change. The results of this study are the process of realizing wooden sculptures starting from the exploration of ideas, shapes, selection of materials, tools, work processes and finishing. The products produced are statues of Garuda Wisnu, Rama Shinta, Hanoman, Chinese Dragon, Kwan Im, Toa Pe Kong, Buddha, Barong, Rangda, Saraswati, Sri, Durga, Lord Shiva, Ganesha and Kwan Sing Tee Koen statues. The ups and downs of wooden sculpture can be seen from 1970. In that year there were about twenty people who were skilled at making sculptures and developing them, for example the statue of Garuda, Ramayana, and others. The existence of these crafts, has marketing opportunities and motivates craftsmen to increase their creativity. When the first Bali bombing occurred, the globalization market, and the corona virus, these crafts experienced a decline, but craftsmen continued to produce these crafts.